2017
DOI: 10.4273/ijvss.8.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Hydrodynamic Journal Bearing Lubrication using Computational Fluid Dynamics and Fluid Structure Interaction Approach

Abstract: Now-a-days, journal bearings are subjected to severe loads and higher operating speeds causing generation of high hydrodynamic pressures which in turn deform the bearing shell thus modifying the lubricating film in the operating region. Hence, there is need for optimized bearing performance parameter estimation considering the realistic change in lubricating film along with less computational time. In this paper, response surface optimization module coupled with static structural and fluent, available in ANSYS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Schweizer [13], in a numerical study, showed that the full floating ring in the journal bearing causes two types of oil film instability internally and externally. Dhande et al [14] dealt with behavioral analysis of the journal bearing using the structure-fluid interaction method and concluded that the combinatory effect of the hydrodynamic force and the elastic behavior resulting from bearing forces shows the deformation of the bearing, and should be considered in order to predict the exact bearing performance in unstable bearing conditions. Gao et al [15] numerically investigated the eccentricity effects of the shaft on the pressure distribution of the water film with different bearing dimensions and rotational speeds and discussed the possibility of instability in the water film.…”
Section: Introductionmentioning
confidence: 99%
“…Schweizer [13], in a numerical study, showed that the full floating ring in the journal bearing causes two types of oil film instability internally and externally. Dhande et al [14] dealt with behavioral analysis of the journal bearing using the structure-fluid interaction method and concluded that the combinatory effect of the hydrodynamic force and the elastic behavior resulting from bearing forces shows the deformation of the bearing, and should be considered in order to predict the exact bearing performance in unstable bearing conditions. Gao et al [15] numerically investigated the eccentricity effects of the shaft on the pressure distribution of the water film with different bearing dimensions and rotational speeds and discussed the possibility of instability in the water film.…”
Section: Introductionmentioning
confidence: 99%
“…Their results for the oil bearing compared closely with those of a Reynolds model and an analytical solution, but no such comparisons were made for the water bearing. Dhande et al [16] developed a CFD model along with FSI to calculate pressures in a laminar oil film including the effects of surface deformation. Their results showed significant pressure-induced surface deformation, especially at high journal eccentricities.…”
Section: Introductionmentioning
confidence: 99%
“…The pre-processing of CFD [9][10][11][12][13] calculation is mainly to establish a fluid model and generate grids. Only by dividing the grids according to the actual flow field 14,15 can make CFD numerical calculation be realised successfully and efficiently.…”
Section: Bearing Fluid Finite Element Model and Mesh Divisionmentioning
confidence: 99%